FROM COLONIAL CAPITALISM TO CRONY CAPITALISM. HISTORICAL AND INSTITUTIONAL DETERMINANTS OF THE SOCIO-ECONOMIC MODEL FROM THE MALAYSIAN PERSPECTIVE - GLINIAK, Pawel (Skhid, 2021)
During the period of colonialism the implementation of colonial capitalism resulted in the integration of Southeast Asia into the global economy, which directly influenced the local socio-economic system. The changes occurring in the region since the 19th century, which is the period discussed in this article, can be analyzed from many points of view. The following paper focuses on the territory of present-day Malaysia, an exceptionally heterogeneous country, and it analyses the results of this transformation and the influence it had on the current socio-economic system. Colonialism has undeniably contributed to the economic growth of the Malay Peninsula while excluding parts of the population and destroying local institutions and existing models of the socio-economic system. Despite this apparent quantitative growth, oligarchic institutions were created, impeding the area's actual qualitative socio-economic development. The decolonization process did not change it sufficiently. The first aim of the article is to indicate the direct historical relationship between colonial capitalism, violently implemented by colonial empires in the conquered territories, and the crony capitalism formed after the decolonization period. Secondly, the author tries to identify oligarchic institutions and the outcomes of their influence. These institutions were created in the historical process within colonial capitalism and are still present today. They fundamentally influence the politics and society of contemporary Malaysia, thus inhibiting qualitative socio-economic transformation. Thirdly, the author, using a variety of indicators and indexes measuring, for example, corruption, the democratization process, or social development, seeks to demonstrate the power of crony capitalism and its institutions and their impact on impeding socio-economic development.